Budaya Ruang dan Strategi Pengembangan Bisnis Mikro (Studi Kasus di Pandeglang) - Agus Lukman Hakim Lukman Hakim (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2018)
Regency is included in the category of underdeveloped regions and has the highest poverty rate in Banten Province. Therefore, the Regional Government of Pandeglang together with the central government has sought to develop the potential of the region with various policies, one of which is the Development of the Special Economic Zone of Tanjung Lesung. Various government policies and the needs of the community, the private sector towards residential space, pushed the northern and southern regions of Pandeglang to experience greater population density. This condition raises a new culture from the local community, namely making the residence and area adjacent to the road as a micro business. The micro business continues to be developed by the government, although it is contrary to the policy of the Pandeglang Regency RTRW.